Design and Implementation of IoT-Based Water Pipe Pressure Monitoring Instrument (Jurnal Elektronika dan Telekomunikasi, 2021)
The water pressure monitoring system in the PDAM pipeline networks has been successfully developed for operation and maintenance of water leaks in a real-time manner. This research aims to design a water pressure monitoring system in operational piping networks to identify anomalies as early as possible. The system is built using a microcontroller, a 1.2 MPa fluid pressure sensor and a control system equipped with a GSM wireless communication module, an Analog to Digital Converter module with 16-bit resolution, a real-time clock peripheral, an OLED display 128x64, and a micro SD card. The developed system was tested in a pressure range of 0.200 - 0.800 bar with 30 repetitions with a RMSE of 0.058 bar. This system has a deterministic coefficient of 0.885 against a standard manometer. The system implemented in the field successfully sends data to the server with a success rate of 96.0%. Data is displayed on a monitoring dashboard that can be accessed via a computer or smartphone.